Impact of Marketing Strategies of Retailers on Consumers with Specific Reference to Ramki Bandi and Local Tiffin Centres - Y. Venkat Reddy; Chamundeshwari Gaddap; Rucha T; Piiyush K; M. Vishnu Vardhan Rao; Samudrala Sharath Chandra (PT Agung Media Publisher, 2024)
Entrepreneurs and small business management go hand in hand in making a successful business. The study is taken up on retailers in the street food industry. The study’s objective is to analyze the impact of the marketing strategies of Ram ki Bandi , a famous street food corner in Hyderabad, India, and a comparative study between the marketing strategies of Ram ki Bandi and local street tiffin centers. Tiffin centers are small eateries put up on the street. A marketing strategy is a long-term plan for achieving a company’s goals by understanding customers’ needs and creating a distinct and sustainable competitive advantage. For the study, the data was collected through primary data sources, such as survey methods, questionnaires, and secondary data sources. The primary data was collected from a sample of 100 respondents using questionnaires and interviews. Marketing strategies are essential in the growth of a retailer’s business. Some of them are as follows: attracting more customers, analyzing competitors, understanding customers, and making optimal pricing decisions, amongst others. The findings of the study state that marking strategies impact consumer behavior when purchasing a given product.